2010
DOI: 10.1152/ajpendo.00600.2009
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of cold-induced brown adipocytes in mouse white fat depots is determined predominantly by white to brown adipocyte transdifferentiation

Abstract: The origin of brown adipocytes arising in white adipose tissue (WAT) after cold acclimatization is unclear. Here, we demonstrate that several UCP1-immunoreactive brown adipocytes occurring in WAT after cold acclimatization have a mixed morphology (paucilocular adipocytes). These cells also had a mixed mitochondrioma with classic "brown" and "white" mitochondria, suggesting intermediate steps in the process of direct transformation of white into brown adipocytes (transdifferentiation). Quantitative electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
540
3
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 667 publications
(606 citation statements)
references
References 67 publications
(92 reference statements)
32
540
3
16
Order By: Relevance
“…Uncoupling protein 1 up‐regulation in response to cold exposure via the stimulation of beta 3‐adrenergic receptors is a remarkable feature of brown36 and beige3 adipocytes. Ectopic Ucp1 expression in ingWAT, for example, increases almost five‐fold following treatment with the beta 3‐adrenergic agonist CL316 17.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncoupling protein 1 up‐regulation in response to cold exposure via the stimulation of beta 3‐adrenergic receptors is a remarkable feature of brown36 and beige3 adipocytes. Ectopic Ucp1 expression in ingWAT, for example, increases almost five‐fold following treatment with the beta 3‐adrenergic agonist CL316 17.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of brown adipocytes to dissipate energy as heat results from the activity of uncoupling protein 1 (UCP1), which is located in the inner mitochondrial membrane and uncouples the electron transport chain from ATP production (extensively reviewed in Cannon and Nedergaard1). In addition to classical brown adipose tissue (BAT) depots, pockets of UCP1‐positive, multilocular adipocytes have also been described within white adipose tissue (WAT) from rodents following cold exposure,2, 3, 4 treatment with a beta 3‐adrenergic agonist,5 or exercise training 6. These adipocytes are commonly referred to as beige, brite (from brown in white), inducible, or recruitable, reviewed in Chechi et al 7 and seem to result from the transdifferentiation of previously unilocular, white adipocytes4, 5 and from the de novo differentiation of precursor cells 8.…”
Section: Introductionmentioning
confidence: 99%
“…16 In the case of brown fat islands present in WAT, it is still debated whether they develop from specific precursors present in WAT or by a true transformation of white to brown adipocytes. 44,45 Whichever is the case, these cells apparently never express Myf5. 16 Consistent with these findings, we did not detect expression of Myf5 in retroperitoneal fat of either ND or HFD rats.…”
Section: Discussionmentioning
confidence: 99%
“…18 The retroperitoneal and inguinal fat pads (but not epididymal fat pads to our knowledge) showed emergence of brown fat (in response to cold or b 3 -stimulation) in several previous studies. 22,45,53 Some of these studies indicated that the capacity for brown fat adipogenesis in WAT depends largely on genetic Figure S5). A full color version of this figure is available at the Hypertension Research journal online.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in fat tissue also accompany cold stress. In general, BAT increases activity and volume with cold stress [10,[34][35][36][37], and recently it has been recognized that cells in white adipose tissue (WAT) can be converted to a brown phenotype by cold exposure [38] (reviewed by [39]). Smith et al have recently visualized significant differences in BAT in mice at ST and TT showing that the lipid to water ratio in BAT is reduced in colder temperatures in accord with its role in thermogenesis [40].…”
Section: Glossarymentioning
confidence: 99%